Effects on Clinical Outcomes of Grafts and Spacers Used in Transforaminal Lumbar Interbody Fusion: a Critical Review. Issue 1 (18th February 2013) - Heida, Kenneth; Ebraheim, Molly; Siddiqui, Saaid; Liu, Jiayong
<x xml:space="preserve">Abstract</x> Transforaminal lumbar interbody fusion (TLIF) is a relatively new and popular spinal fusion technique that has proven very useful since its introduction. To date, fusion rates for different combinations of modalities and materials have not been thoroughly compared and assessed. In this review of published reports, 29 papers met criteria for assessing fusion rates for three different interbody spacers and four different combinations of bone grafts and extenders. The spacers included Capstone, polyether ether ketones and Telamon cages, and the grafting materials reviewed were locally harvested bone, iliac crest bone with local, local bone plus recombinant human bone morphogenetic protein 2 and a mixture of local and allograft bone. Of these, it was found that only the Capstone cage and locally harvested bone achieved statistically significant higher fusion rates (96.46% ± 2.89% and 97.07% ± 1.94% respectively) than the other modalities and materials studied. Oswestry Disability Index scores and visual pain scales were also examined as indicators of overall improvement after using each spacer and graft; the Telamon cage and local bone mixed with rhBMP‐2 stood out as conferring statistically significant greater improvements according to these two scales. Our findings are that Capstone and locally harvested bone alone are relatively superior in terms of fusion rates.